MENGOPTIMALKAN PERAWATAN WASTE OIL INCENERATOR UNTUK PEMBAKARAN MINYAK KOTOR DI ATAS KAPAL - Sumali, Bambang; Diyatmiko, Fadli; Sabila, Qhattrunnada Priwidia; Ahmed, Gibraltar Priwidia (UNIMAR AMNI Semarang, 2024)
In accordance with the provisions and regulations in Marpol 73/78 concerning regulations for preventing marine pollution. And Marpol 73/78 Annex III regarding burning oil and waste using a Waste Oil Incinerator, requires knowledge, ability and responsibility for handling it. This world is always developing in the field of waste processing, especially those originating from ships, generally from the Engine Room, so it is better for ships to be equipped with Waste Oil Incinerator, which is a tool commonly used to burn dirty oil and other rubbish and debris on ships that can be burned. Considering its very important role on ships, the Waste Oil Incinerator is very useful and is very important equipment in efforts to prevent pollution at sea. Therefore, maintenance of the Incinerator must be carried out. With routine maintenance and repairs and in accordance with correct maintenance planning, it will provide large economic benefits for the company and participate in preserving marine ecosystems and the marine environment. However, in its implementation, errors often occur which cause a decrease in the quality of the Waste Oil Incinerator, thus damaging the marine ecosystem due to several things as follows: 1) TheWaste Oil Incinerator does not work optimally 2) Lack of maintenance of the Main Burner Incinerator on board the ship 3) Lack of maintenance on the Waste Oil Incinerator 4) Operation of the Waste Oil Incinerator not in accordance with the instructions manual.